1971
DOI: 10.1063/1.1674866
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Vibrations of Molecular Solids. X. CH3CCl3, CD3CCl3, CH3CCl2H, and CH3CF3

Abstract: The far-infrared spectra of solid CHaCCIa and CDaCCla have been investigated from 33 to 400 cm-l . Raman spectra of these solids have also been recorded. The internal torsional mode was observed at 290 and 206 cml in the infrared spectra of solid methylchloroform and methylchloroform-da, respectively. The threefold periodic barrier to rotation was calculated to be 5.5 kcal/mol. This barrier is compared to those previously reported by other techniques for this molecule and the reported value is much larger than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…To complicate the situation, relative intensity measurements in the microwave spectrum gave a barrier, V 3 = 1.74 (30) kcal mol À1 [9] in good agreement with the thermodynamic determination. Furthermore, the torsional frequency obtained from the neutron scattering study value was confirmed by a Raman study in solid phase which gives m s = 290 cm À1 [10]. This last result prompted a new microwave study and, from the relative intensities of the rotational transitions in ground and excited vibrational states, the frequency of the torsional mode was found to be 276(10) cm À1 [11].…”
Section: Introductionsupporting
confidence: 55%
“…To complicate the situation, relative intensity measurements in the microwave spectrum gave a barrier, V 3 = 1.74 (30) kcal mol À1 [9] in good agreement with the thermodynamic determination. Furthermore, the torsional frequency obtained from the neutron scattering study value was confirmed by a Raman study in solid phase which gives m s = 290 cm À1 [10]. This last result prompted a new microwave study and, from the relative intensities of the rotational transitions in ground and excited vibrational states, the frequency of the torsional mode was found to be 276(10) cm À1 [11].…”
Section: Introductionsupporting
confidence: 55%
“…This argument, when combined with relative intensity considerations, made it possible to assign new bands to the next higher unassigned excited vibrational states in 35 Cl 3 CCH 3 , namely second lowest A-symmetry mode, m 5 and the second lowest E-symmetry mode, m 11 . Ab initio calculations and the available information on the infrared spectrum [14] indicated that the wavenumbers for these modes are both in the 350 cm À1 region. There is still a problem in that it was unlikely that the bands X 1 ; X 2 reflected interstate interactions completely since the progressions of lines away from the bandheads were in both bands in the same direction.…”
Section: Rotational Spectrummentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8][9][10][11] Thanks to the considerable mass difference, for example ca. 100 % mass increase from protium ( 1 H) to deuterium ( 2 H or D) and the different nuclear spin as well, the isotope effect is more pronounced in further affecting the associated inter/intramolecular behavior, like the strength of hydrogen bond, [12][13][14] the lattice vibration/ spin-phonon coupling, [15][16][17][18][19] and the much smaller gyromagnetic ratio of the deuterium spin ( 2 H: 1 H = 1:6.5). As a weakly interacted monodisperse system, single-molecule magnets (SMMs) exhibit slow magnetic relaxation arising from their large magnetic anisotropy, which shows the ability of magnetic memory at the single-molecule level.…”
mentioning
confidence: 99%